IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 56 TAHUN 2015 TENTANG KODE DAN DATA WILAYAH ADMINISTRASI PEMERINTAHAN (Studi Di Kabupaten Kampar Dan Kabupaten Rokan Hulu) - Monalisa, Monalisa; Andriyus, Andriyus; Uyun, Rafida (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
This study aims to find out the Implementation Of The Minister Of Home Affairs Ministerial Regulation Number 56 of 2015 On Codes and Data Of Administrative Regions Of Government (Studies in Kampar and Rokan Hulu districts). Theory used in this research is Edward III theory include; Communication, Resources, Disposition, and Bureaucratic Structure. This type of research is qualitative type, and the research location is 5 (five) villages, Tanah Datar village, Intan Jaya village, Muara Intan village, Rimba Jaya village, and Rimba Makmur village in Kampar and Rokan Hulu districts. There are 14 people who made the informant in this research data, researcher use interview in this research, after the data collected and will be analyzed descriptively, to get answer about Implementation of Implementation of this ministerial regulation. After conducting in-depth research and interviews, the result of research on the Implementation Of the Minister of Home Affairs Ministerial Regulation number 56 of 2015 on codes an data on administrative areas of Kampar regency and Rokan Hulu district are “Adequately Implemented”, with some obstacles such as the non-establishment of the boundary between Kampar regency and Rokan hulu district so that there is still a dualism system of government. The regulation of the minister of home affairs number 56 of 2015 only stipulates the code of the administrative area of government as the identity of an administrative area so that it does not necessarily confirm the boundaries of the antecedents of the adjacent districts so that border-related matters are still often conflicts as long as there is no such boundary agreement and the territorial code can still change if a boundary agreement has been reached.